Instruments for Measuring the Activity of the European Ombudsman - IGNAT, Claudiu (Journal of Advanced Research in Law and Economics, 2019)
The European Ombudsman as an institution for the protection of citizens' rights to good administration and good governance has a number of mechanisms comprising control measures in terms of both its activity and its efficiency. The Ombudsman’s role is not only to notify the relevant institutions of the public administration entitled to settle the notification but, on the contrary, it is able to follow the settlement and implementation of the administrative decision requested by the ombudsman.